Proposal Of Marketing Communication Strategy To Accelerate Adoption And Diffusion Process Of Gentle Birth - Sarastri, Pramudita; Purwanegara, Mustika Sufiati (The Indonesian Journal of Business Administration, 2012)
The number of birth will always increasing. Based on the results of Census 2010, population is increasing about 1.96 percent each year. With a population of 2, 39 million, each year is estimated to 62.617 babies born in the city of Bandung.The purpose of this study was to explore the insights of pregnant women in order to create a strategy to accelerate the adoption and diffusion process for the philosophy of Gentle Birth.This research technique is using qualitative methods that apply ethnography method which consists of in-depth interviews, netnography, and videography. The purpose of using this technique is to analyze psychographic of pregnant women to explore in depth insight. In-depth interviews and observations conducted in Bandung in April-July 2012, on the 12 (twelve) of the respondents with the criteria were pregnant and the second trimester. Netnography conducted on discussion forums on the Internet which consists of Mommies Daily and Gentle Birth for All and observing conversations in the forums labeled "Gentle Birth", "Normal Delivery VS Caesar", "water birth", and "C-section".Finding of this research results there are three psychographic segmentation of expectant mothers that generate of motivation toward birthing. Segment A is a segment that wants to do a normal birth more than anything. Segment B placed her child safety as priority without no matter what procedure that must be endured. The last is segment C is choosing C-section because she want to avoid pain. The author determine segment A and segment C as a psychographic target.Insight came from the research was â€œMothers are having an amazing experience and she want to get through it with comfort,â€ Based on that idea, a campaign concept was then developed with objective to create awareness about brand and product.The tactics was using internet marketing, publicity, and personnel communication channel that was selected based on cost-effective consideration.Â  The overview of implementation strategy are using social media as a tool of communication, penetrate to mother and baby communitiies and maximize the utility of customer service. Key Words: gentle birth, adoption dan diffusion, marketing communication, qualitative research, insight.